2021
DOI: 10.5435/jaaos-d-20-00786
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Gap: The Influence of Foot and Ankle Pathomechanics in Total Knee Arthroplasty

Abstract: Altered spinopelvic mechanics can have dramatic influences on the success of hip arthroplasty as seen with concomitant hip and spine disease. Interestingly, limited focus has been directed toward a similar codependent relationship between concurrent knee and foot deformities. By bridging this interdisciplinary gap, we attempt to explore the current understanding and clinical implications of concomitant knee and foot pathology while reviewing management options for addressing this unique yet ubiquitous patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In a retrospective study, Norton et al identified compensatory hindfoot alignment after TKA and where it occurred among those with end‐stage OA undergoing TKA [28]. In a recent review article, Naylor et al summarized the potential involvement of the ground KA as the evaluation axis when considering both hindfoot and knee alignment changes after TKA [27]. In the current study, ankle/foot deformities were excluded to avoid compensatory hindfoot alignment changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective study, Norton et al identified compensatory hindfoot alignment after TKA and where it occurred among those with end‐stage OA undergoing TKA [28]. In a recent review article, Naylor et al summarized the potential involvement of the ground KA as the evaluation axis when considering both hindfoot and knee alignment changes after TKA [27]. In the current study, ankle/foot deformities were excluded to avoid compensatory hindfoot alignment changes.…”
Section: Discussionmentioning
confidence: 99%
“…Haraguchi et al suggested that true MA, previously known as the ground MA [5, 26], should be assessed from the hip center to the lowest point of the calcaneus, rather than the ankle center [8]. Recently, full‐length leg assessment, including that of the calcaneus, has attracted attention as an alternative alignment assessment [17, 19, 20, 27]. Following this concept, Matsumoto et al reported on a tibia‐restricted modified KA‐TKA procedure [23], in which the femoral component was placed on the cylindrical axis using the calipered technique, and the tibial component was constantly placed at 3° varus.…”
Section: Introductionmentioning
confidence: 99%
“…5 Examination of the entire lower limb including the foot and ankle is important as the hind foot affects the mechanical axis of the lower limb, and coronal hindfoot deformity may affect knee mechanics after TKA (Figure 1). 18 but may have hind foot valgus. 18 It has been suggested that the hindfoot deformity should be addressed prior to TKA to minimise abnormal stress on the implant; however, other authors feel that hind foot alignment does improve post TKA but residual problems should be noted and addressed if the correction is inadequate.…”
Section: Clinical Examinationmentioning
confidence: 99%
“…The hip-to-calcaneus axis, known as the ground mechanical axis (MA) [6,7], passes through the center of the knee joint in the native knee [8]; it has attracted attention as an alternative alignment assessment to the hip-to-talus axis, the gold standard MA [9][10][11]. Matsumoto et al reported a tibia-restricted modified KA-TKA procedure [12], where the femoral component was placed on the cylindrical axis using the calipered technique, and the tibial component constantly placed at 3° varus.…”
Section: Introductionmentioning
confidence: 99%